Enhanced Stature in the Elderly: The Immediate Impact of Acute Postural Exercises - Arnulfo Ramos-Jiménez; Ismael Antonio García-Hernández; Isaac Armando Chávez-Guevara; Rosa Patricia Hernández-Torres; Miguel Murguía-Romero; José Miguel Martínez-Sanz; Marco Antonio Hernández-Lepe (MDPI AG, 2024)
This study investigates the immediate effects of acute postural exercises on the stature of seniors, focusing on changes in both upright and supine stature measurements. A within-subject design with repeated measures was applied, involving seniors participating in continuous exercises aimed at enhancing core musculature strength and promoting muscle relaxation. Stature measurements were recorded pre- and post-exercise in both upright and supine positions, alongside assessments of body mass index (BMI) category classifications. The results revealed a post-exercise increase in stature ranging from 0.9 to 6.0 cm and from 0.2 to 7.2 cm in upright and supine positions, respectively, with an average increase of approximately 3.5 cm in both upright and supine positions. Statistically significant and clinically relevant changes were observed (p < 0.05), including a modification of BMI by approximately two units, reclassifying 55% of participants from overweight or obese to normal weight or overweight. Furthermore, the similarity between post-exercise upright stature and pre-exercise supine stature suggested that the supine position might provide a more accurate measure of stature in seniors. Conclusively, acute postural exercises have an immediate positive impact on the stature of seniors, suggesting their potential utility in clinical settings for accurate stature measurement. However, BMI results should be interpreted with caution because they are only related to the acute change in stature and therefore may lead to the misinterpretation of the study findings, so future studies focused on evaluating the chronic effect of postural exercises integration on the health outcomes of older adults are needed to demonstrate their potential utility in clinical settings to improve postural health and general well-being.